Photoresponsive Cucurbit[8]uril‐Mediated Adhesion of Bacteria on Supported Lipid Bilayers. Issue 46 (15th October 2015) - Sankaran, Shrikrishnan; van Weerd, Jasper; Voskuhl, Jens; Karperien, Marcel; Jonkheijm, Pascal
Abstract : In this work, the development of a photoresponsive platform for the presentation of bioactive ligands to study receptor–ligand interactions has been described. For this purpose, supramolecular host–guest chemistry and supported lipid bilayers (SLBs) have been combined in a microfluidic device. Quartz crystal microbalance with dissipation monitoring (QCM‐D) studies on methyl viologen (MV)‐functionalized oligo ethylene glycol‐based self‐assembled monolayers, gel and liquid‐state SLBs have been compared for their nonfouling properties in the case of ConA and bacteria. In combination with bacterial adhesion test, negligible nonspecific bacterial adhesion is observed only in the case of methyl‐viologen‐modified liquid‐state SLBs. Therefore, liquid‐state SLBs have been identified as most suitable for studying specific cell interactions when MV is incorporated as a guest on the surface. The photoswitchable supramolecular ternary complex is formed by assembling cucurbit[8]uril (CB[8]) and an azobenzene–mannose conjugate (Azo–Man) onto MV‐functionalized liquid‐state SLBs and the assembly process has been characterized using QCM‐D and fluorescence techniques. Mannose has been found to enable binding of E. coli via cell‐surface receptors on the nonfouling supramolecular SLBs. Optical switching of the azobenzene moiety allows us to "erase" the bioactive surface after bacterial binding, providing the potential to develop reusable sensors. Localized photorelease of bacterial cells has also been shown indicating the possibility of optically guiding cellular growth, migration, and intercellular interactions. Abstract : Specific E. coli binding and localized photoswitchable release are achieved using supramolecular chemistry, host–guest interactions, and supported lipid bilayers. In this study, ternary complexes of host molecule cucurbit[8]uril and photoswitchable glycoconjugate guest azobenzene‐mannose form successfully on methyviologen‐modified supported lipid bilayers. The proposed system with good nonfouling properties paves the way for the design of reusable biosensors that allow dynamic presentation of bioactive ligands.